OMAH MELEK: MENCIPTAKAN PEMUDA MUHAMMADIYAH KARANGPLOSO YANG KRITIS, PEKA DAN PARTISIPATIF - Sulaiman, Ahmad; Mashuri, Muhammad Fath (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Together with Muhammadiyah’s youths of Karangploso as partners, this study proposed an educational and community empowerment program called OMAH MELEK. The approach adapted to OMAH MELEK is a 'problem-posing' approach which is introduced by the infamous critical pedagogy scholar from Brazil: Paulo Freire. This method includes identifying problems close to the subject's life, as well as allowing the subject to deliberatively produce solution for the problems. Instead of becoming an observer, the problem-posing method assign the facilitator an active role in solving problems with the subject. The main objective was to build critical awareness among Muhammadiyah youth members and thus to be critical, sensitive, and participatory. The results of this program indicated that the partners are becoming more active, involved in regional development and have organizational programs that run continuously.